The Onion Routing Performance using Shadow-plugin-TOR - Hartanto Kusuma Wardana; Liauw Frediczen Handianto; Banu Wirawan Yohanes (IAES Indonesia Section, 2017)
Anonymous network provides user privacy to protect identity. The onion routing (TOR) project is one kind of Internet anonymous networks which attracts many researchers and clients nowadays, because of its simplicity and scalability. However, there are some difficulties to analyze TOR performance within live TOR networks since it is distributed and its security nature. This paper presents a TOR network simulation using shadow-plugin-TOR to configure a small scale virtual computer network within a host, running TOR, and then to analyze TOR performance in several measurements. One main advantage is that the shadow-plugin-TOR application can be implemented within a host in which used to build a client-server architecture of TOR network. Various number of relays and clients have been set to examine TOR network performance. The small scale simulations conducted using maximal CPU capacity between 60%–75% and memory (RAM) usage between 320 MiB– 1.5 GiB for each configuration. The simulation results show that average transmission time is shortened and bandwidth is faster along with increasing number of relay rather than adding more client.